“The Referee Plays to Be Insulted!”: An Exploratory Qualitative Study on the Spanish Football Referees’ Experiences of Aggression, Violence, and Coping - Devís-Devís, José; Serrano-Durá, José; Molina, Pere (Frontiers in Psychology, 2021)
Referees are essential participants in the sport of football with the mission to enforce the rules and achieve the necessary fairness during the matches. They are often target of hostile reactions from fans, players and coaches. However, few studies have focused on these experiences and the strategies they use to manage them. In order to fill this gap, a qualitative interview-based study was developed to explore the experiences of a group of football referees (four male and four female) on aggression, violence and coping. A thematic analysis was developed combining inductive and deductive processes. Results indicated that the most frequent aggressions experienced were verbal abuse. Most of the aggressions from spectators were of a sexist nature. When aggressions were considered normal by referees, symbolic violence emerged. Racist aggressions were directed to the two Moroccan participants. Problem and emotional-focused coping strategies were identified. The two most common referee responses to coaches’ and players’ verbal abuse were penalties and send off calls. Smiling and not considering insults as a personal matter were two emotional-focused coping strategies used toward spectator aggressions. Implications for the referees’ job and well-being, as well as the quality of football competitions were highlighted to reduce aggressions and violence, and to help referees cope with hostile behaviors.